Gifted Students' Actualization of a Rich Task's Mathematical Potential When Working in Small Groups - Anita Movik Simensen; Mirjam Harkestad Olsen (MDPI AG, 2024)
This article examines gifted students' (ages 13-16) groupwork on a rich task in mathematics. This study was conducted in Norway, which has an inclusive education system that does not allow fixed-ability grouping. The purpose of this study was to better understand how to cultivate mathematical learning opportunities for gifted learners in inclusive education systems. The analysis was conducted from a multimodal perspective, in which students' coordination of speech, gestures, and artifact use was viewed as part of their learning process. The findings contribute to discussions on gifted students as a heterogeneous group. Moreover, our analysis illustrates how giftedness can be invisible, leading to unrealized potential and low achievement. We suggest that more attention be paid to teaching by adapting to gifted students' individual needs, particularly if the intention is to provide high-quality learning opportunities for gifted students in inclusive settings.